Studi Kualitas Fisik-Kimiawi dan Organoleptik Sosis Ikan Lele Dumbo (Clarias Gariepinus) Akibat Pengaruh Perebusan, Pengukusan dan Kombinasinya dengan Pengasapan - Widjanarko, Simon Bambang; Zubaidah, Elok; Kusuma, Aan Muzaky (Jurnal Teknologi Pertanian, 2003)
This paper reported the quality of cat fish sausages effected by methods of cookings. The aims of the experiment is to study the effect of cooking by means of broiling, steaming and combining broiling and smoking as wells as steaming and smoking. Randomized Block Design Non Factorial had been used in this experiment, each treatments replicated 3 times. Results showed that, the best treatment on the basis of sensory test was steaming sausages at 100 0 C for 15 minutes without smoking processes. Sausages had moisture content 66,46%, protein content 60,35% b.k. (20,81% b.b.), total fat content 6,29%, Aw 0,903, flesh texture 0,017 mm/g.sec, a taste score 5,2 (moderate like), flavour score 4,75 (moderate like), colour score 4,50 (moderate like), teeth texture 4,75 (moderate like). Methods of cooking also significantly effects quality of cat fish sausages. Â  Keyword: cat fish, cooking methods, and cooking effect